(untitled) (ENTHYMEMA, 2025)
The article analyzes the use of the metaphor of "flow" in the cultural context of the second half of the 18th century, with particular attention to that debate, epistemological as well as aesthetic, which prepares and accompanies the ongoing literary revolutions and, in particular, the birth of the modern novel. The metaphor of "flow" is analyzed as a catalyst of a broader metonymic field relating to images and concepts of liquidity, ambiguity, volatilization of reality, etc., and, more generally, as a concretion of a gradual crisis of the stable foundations of the episteme. It is precisely this crisis, in its manifestations in different debates and in different disciplines, that is underlined by the metaphor on the table, as it is in turn connected to the social, political and economic upheavals underway at the time.